2014
DOI: 10.1371/journal.pone.0089428
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prolactin Levels Are Associated with Impaired Processing Speed in Subjects with Early Psychosis

Abstract: Hyperprolactinaemia, a common side effect of some antipsychotic drugs, is also present in drug-naïve psychotic patients and subjects at risk for psychosis. Recent studies in non-psychiatric populations suggest that increased prolactin may have negative effects on cognition. The aim of our study was to explore whether high plasma prolactin levels are associated with poorer cognitive functioning in subjects with early psychoses. We studied 107 participants: 29 healthy subjects and 78 subjects with an early psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…However, a similar result to our findings is reported by Montalvo et al (2014). In this study the patients with brief evolution of psychosis displayed a lower cognitive performance associated with the effect of prolactin, especially in men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, a similar result to our findings is reported by Montalvo et al (2014). In this study the patients with brief evolution of psychosis displayed a lower cognitive performance associated with the effect of prolactin, especially in men.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to cognitive symptoms, studies with high risk for psychosis individuals show a negative correlation between prolactin levels and performance of reasoning, problem solving, and general cognition tasks (Labad, 2019). Moreover, Montalvo et al (2014) reported a negative correlation between prolactin levels and processing speed tests performance in patients with first episode psychosis. Finally, Yao et al (2018) described a significant negative correlation between verbal memory and cognitive flexibility performance and hyperprolactinemia in women with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that circadian rhythms control sleep and biological processes including cell regeneration, core body temperature variations, and hormone metabolism (Buysse et al ., 2005; Sharma and Kavuru, 2010). There is also evidence that changes in the metabolism, especially disorders of the thyroid function, may be associated with cognitive decline (Smith et al ., 2002) and specifically decrease in speed of processing (Montalvo et al ., 2014; Smith et al ., 2015). Furthermore, changes in the thyroid, especially hypothyroidism, is considered a reversible cause of secondary dementia in older adults (Horvath et al ., 1989; Cummings, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, during the last few years, with increased research into cognition as a nuclear dimension of serious mental disorders (schizophrenia and related psychotic disorders, bipolar disorder), various studies have evaluated the function of prolactin in the cognition spectrum. One study of patients with early psychosis (less than three years since the first signs of symptoms) showed that elevated levels of prolactin were associated with deficits in processing speed independent of the use of antipsychotic drugs ( Montalvo et al, 2014 ). There is considerable controversy surrounding these results, however, because another study of cognition in male patients with schizophrenia demonstrated that prolactin did not interfere with the link between sex steroids, such as testosterone, and cognitive function ( Moore et al, 2013 ).…”
Section: Cognition and Prolactinmentioning
confidence: 99%